Advances in pharmacotherapy for head and neck cancer. (13th October 2021) - kumar, Shikhar; Noronha, Vanita; Patil, Vijay; Joshi, Amit; Menon, Nandini; Prabhash, Kumar
ABSTRACT: Introduction: Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers worldwide and is a leading cause for cancer-related mortality. This review attempts to give a comprehensive summary of the recent developments in pharmacotherapeutic options for locally advanced/metastatic HNSCC. Areas covered: In this review, the authors conducted a systematic literature search for published articles on HNSCC in the PubMed database using the keywords 'head and neck squamous cell carcinoma or HNSCC, ' 'targeted therapy, ' 'immunotherapy.' The search was restricted to meta-analyses, clinical trials, practice guidelines, and abstract presentations at international meetings. The final search encompassed articles published from 2010 to 2021. Articles published in languages other than English were excluded. Expert opinion: Immune checkpoint inhibition has been the most significant advance in the treatment of R/M HNSCC. Oral metronomic therapy has emerged as an important therapeutic option for low to middle-income countries. H-RAS inhibition is one of the most promising areas of research.